A laboratory investigation and numerical modeling on fiber reinforced lime and alkaline binder stabilized pavement subgrade soil - Mazhar Syed; Anasua GuhaRay; Sai Kiran Chukka; Subhan Ahmad (Case Studies in Construction Materials, 2024)
The differential settlement and excessive deflection in expansive subgrade soils lead to low volumetric stability upon moisture imbalance and cause severe damage to highway and airport field pavement surfaces. The present paper attempts to strengthen the stability behavior of expansive subgrade soil using an envirosafe alkaline binder (AB) with polypropylene fiber (PLF). AB was produced by combining dry aluminosilicate precursors (steel slag [SS] and sugarcane bagasse ash [SBA]) with a liquid activator (mixture of sodium hydroxide [NaOH] and sodium silicate [Na2SiO3]) in 0.4 water to binder (w/b) ratio. California bearing ratio (CBR) based resilient modulus, shear strength ratio (Sr), and consolidation tests were conducted as performance indicators of expansive subgrade soil reinforced with discrete PLF (0–0.5%) in 6% lime and 6% alkaline binder. The study also proposes the optimal sugarcane bagasse ash-steel slag-PLF dosage in the AB-stabilized subgrade layer. Moreover, mineralogical and morphological studies using powder X-ray diffraction (XRD) and field emission scanning electron microscopy (FE-SEM) were also carried out to understand the crystalline compounds and micro surface texture of the soil-fiber mixture. It was revealed that AB-fiber-soil exhibits higher interfacial frictional bonding and interlocking density than lime-fiber-soil. Also, 2D finite element analyses were carried out to compare the behavior of subgrade under the influence of vehicular load on the surface. PLF-AB soil mixture shows 72% lower vertical deformation than unstabilized expansive soil. Based on the findings of this study, recommendations for the practical application of stabilizing expansive subgrade soils were proposed.